SMART approach to spine clinical research - Lee, Michael J.; Norvell, Daniel C.; Dettori, Joseph R.; Skelly, Andrea C.; Chapman, Jens R. (AOSpine ; Distribution by Thieme Verlag, 2013)
"Planning, conducting, and publishing the results of your clinical research can be a long and arduous journey. The SMART Approach to Spine Clinical Research presents and explains the many interrelated components essential to spine clinical research in an easily accessible way, guiding you step-by-step through the principles and methods of planning and evaluating clinical research."--